Influence of modified pent roof combustion cavity on diesel engine performance and emission characteristics. Issue 8 (17th November 2019) - Karikalan, L.; Chandrasekaran, M.; Ramasubramanian, S.; Vivek, P.
ABSTRACT: The utmost vital role of the IC engine burning chamber is to offer correct mixing of air and fuel in a little time to lessen the ignition lag phase, which determines the quality of the combustion, performance and the exhaust emission characteristics. To attain this, a systematised air movement termed 'air swirl' is offered to create high comparative velocity amongst fuel droplets and air. In this work, the engine piston head is modified to a 6° angle at the crown part, and the engine performance and emission analysis are carried out. The modified piston promotes speedier mingling between the inducted air and injected fuel, which speeds up the combustion process. By modifying the combustion chamber, we obtained a very less amount of NO x Emissions and a moderate amount of hydrocarbon and carbon monoxide emissions.